The fairness of victim participation in the parole process from an offender perspective - Oliver, Charles (Acta criminologica, 2019)
Victim input at the parole decision-making process has become an integral part of corrections in South Africa during the last decade. A question that could be raised, however, has to do with the extent to which this development affects the rights of offenders. Providing more rights to victims, after all, does not necessarily mean that justice will be better served towards all concerned. The problem is that the development of the parole process, since Maconochie’s initial idea of placing the responsibility for reform in the hands of the offender, has changed significantly. With the introduction of the Rehabilitation Model in the 1920s, parole decisions were taken based on the opinions of ‘experts,’ with the result that proper due process rights for offenders were deemed unnecessary. Victim input in parole deliberations differ from rehabilitation in the sense that an adversarial situation could be created in the parole process when most victims oppose parole. To ensure fairness under such a situation, it is important that offenders should have the right to defend themselves. The current system, which holds that parole release should be viewed as a privilege and not a right, lacks in this regard with very few due process rights available to offenders. This may result in the misuse of parole by victims and other parties. The fact that even more variables are brought into play that may lead to parole being refused can also lead to an erosion of offenders’ control over their lives which could result in a sense of injustice and offenders giving up on attempts to rehabilitate themselves.